Development of a Family-Based Early Intervention Program to Improve Consonant Letter Articulation Skills in Children with Articulation Barriers - Bela, Muhammad Rafi Wirdan Assyakir Tandu; Susetyo, Budi; Rizqita, Alya Jilan; Khoshsimov, Maksud (Indonesian Journal of Community and Special Needs Education, 2024)
This study aims to develop a family-based early intervention program for children with articulation barriers who attend inclusive schools. The method used in this research is descriptive qualitative to develop a family-based early intervention program. The subject in this study is a 6-year-old child who has barriers in his articulation ability. The subject currently attends a kindergarten in Bandung, West Java, Indonesia. The result of this study is a family-based early intervention program to train articulation skills in children. This research is expected to be a reference for various parties, such as parents, teachers, and special education teachers in developing articulation skills owned by children with articulation barriers.